2011
DOI: 10.1007/s11481-011-9278-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuronal Ferritin Heavy Chain, A New Player in Opiate-Induced Chemokine Dysfunction

Abstract: The heavy chain subunit of ferritin (FHC), a ubiquitous protein best known for its iron-sequestering activity as part of the ferritin complex, has recently been described as a novel inhibitor of signaling through the chemokine receptor CXCR4. Levels of FHC as well as its effects on CXCR4 activation increase in cortical neurons exposed to mu-opioid receptor agonists such as morphine, an effect likely specific to neurons. Major actions of CXCR4 signaling in the mature brain include a promotion of neurogenesis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Our previous studies demonstrated the regulation of FHC by morphine and the specific involvement of MORs in this effect (27,57); in vivo or in vitro deletion of FHC in neurons abolished the inhibitory action of morphine exposure on CXCL12/CXCR4 signaling, emphasizing the importance of the FHC/CXCR4 interaction promoted by morphine. Here, we extend these findings to show a similar effect caused by HIV infection in the absence of opiate exposure.…”
Section: Discussionmentioning
confidence: 87%
“…Our previous studies demonstrated the regulation of FHC by morphine and the specific involvement of MORs in this effect (27,57); in vivo or in vitro deletion of FHC in neurons abolished the inhibitory action of morphine exposure on CXCL12/CXCR4 signaling, emphasizing the importance of the FHC/CXCR4 interaction promoted by morphine. Here, we extend these findings to show a similar effect caused by HIV infection in the absence of opiate exposure.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, additional functions have been explored for FTH1, and connections to major signaling pathways have been established. It acts as an inhibitor of signaling exerted by the chemokine receptor CXCR4 in cortical neurons (Abt and Meucci 2011). Ferritin, the spherical molecule of 24 subunits of FTH1 and FTL (ferritin light chain), not only stores iron within cells, but has also been found in the circulation and binds to different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…There are seven reviews, five original contributions and one brief report. In the reviews by Roy et al, Abt and Meucci and Wang et al, the current status of the consequence of opiates on immune function and opportunistic infection are highlighted (Abt and Meucci 2011;Roy et al 2011;. Although opioid-induced immunosuppression has been demonstrated in cell culture experiments and in animal models, there is a paucity of confirmatory studies in humans.…”
Section: Opportunistic Infections Immune Disfunctionmentioning
confidence: 99%